Acute Increase of Children's Conjunctivitis Clinic Visits by Asian Dust Storms Exposure - A Spatiotemporal Study in Taipei, Taiwan - Chien, Lung-Chang (Public Library of Science, 2014)
Adverse health impacts of Asian dust storms (ADS) have been widely investigated and discussed in respiratory disease, but no study has examined the association between ADS events and their impact on eye diseases, especially in children. The impact of ADS events on the incidence of children's conjunctivitis is examined by analyzing the data from children's clinic visits registered in the 41 districts of Taipei area in Taiwan during the period 2002–2007. The structural additive regression modeling approach was used to assess the association between ADS events and clinic visits for conjunctivitis in children with consideration of day-of-the-week effects, temperature, and air quality levels. This study identifies an acute increase in the relative rate for children's conjunctivitis clinic visits during ADS periods with 1.48% (95% CI = 0.79, 2.17) for preschool children (aged <6 years old) and 9.48% (95% CI = 9.03, 9.93) for schoolchildren (aged ≥6 years old), respectively. The relative rates during post-ADS periods were still statistically significant, but much lower than those during ADS periods. The spatial analysis presents geographic heterogeneity of children's conjunctivitis clinic visits where higher relative rates were more likely observed in the most populated districts Compared to previous ADS studies related to respiratory diseases, our results reveals significantly acute impacts on children's conjunctivitis during ADS periods, and much influence on schoolchildren. Vulnerable areas were also identified in high density population.